Seven Operation Modes and Simulation Models of Solar Heating System with PCM Storage Tank - Juan Zhao; Yasheng Ji; Yanping Yuan; Zhaoli Zhang; Jun Lu (Energies, 2017)
A physical model and dynamic simulation models of a solar phase-change heat storage heating system with a plate solar collector, phase-change material (PCM) storage tank, plate heat exchanger, and auxiliary heat sources were established. A control strategy and numerical models for each of seven different operation modes that cover the entire heating season of the system were developed for the first time. The seven proposed operation modes are Mode 1: free cooling; Mode 2: reservation of heat absorbed by the solar collector in the PCM storage tank when there is no heating demand; Mode 3: direct supply of the heating demand by the solar collector; Mode 4: use of the heat absorbed by the solar collector to meet the heating demands, with the excess heat stored in the PCM storage tank; Mode 5: use of heat stored in the PCM storage tank to meet the heating demands, Mode 6: combined use of heat stored in the PCM storage tank and the auxiliary heating sources to meet the heating demands; and Mode 7: exclusive use of the auxiliary heat sources in order to meet the heating demands. Mathematical models were established for each of the above seven operation modes, taking into consideration the effects of the outdoor meteorological parameters and terminal load on the heating system. The real-time parameters for the entire heating season of the system with respect to the different operation modes can be obtained by solving the simulation models, and used as reference for the optimal design and operation of the actual system.